KARAKTERISTIK ORANG DENGAN HIV/AIDS DI KOTA MANADO - Rahmadhani, Hasdalia; Kaunang, Wulan P.J (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 1 (2023): April 2023, 2023)
HIV/AIDS continues to be a major global health problem that gradually attacks and weakens the immune system, making it easier for diseases to enter the patient's body. This is called an opportunistic infection which eventually causes death. The age, sex, CD4 count, profession, and other characteristics of people with HIV/AIDS vary. This study aims to identify the characteristics of people with HIV/AIDS in Manado City. The research was conducted using descriptive observational methods at the Batamang Plus Manado Foundation with 1044 data as samples. The variables used were age, sex, risk factors, and duration of HIV. The results found that most people with HIV/AIDS are between 26-35 years old, male, the most dominant risk factor was transmission was MSM/Homo, and the longest duration was 10 years. HIV/AIDS prevention plans and programs must focus on the right target, and educational institutions must provide sex education early to prevent HIV/AIDS transmission. Keywords : Characteristic, HIV, AIDS